Development of Waste Pollution Module with Argument Driven Inquiry (ADI) Model for Students - Diartika, Eka Imbia Agus (Asian Journal of Multidisciplinary Research, 2024)
This research aims to develop a waste pollution module using the Argument Driven Inquiry (ADI) model. The module was developed using the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The validity of this development module refers to the results of validation by validators who are teaching materials experts, material experts and field practitioners. The practicality of this module refers to the results of assessments by users (students). The research results show that the module developed meets validity and practicality. The module validity percentage according to the teaching subject expert validator was 93.26%, the matter expert was 100%, and the field practitioner was 95.12%. The percentage of practicality according to the students responses questionnaires were 80.53%.